Sustainable entrepreneurship: the scientific production of the 21st century - Silveira, Amelia; Backes, Danieli Artuzi Pes; Kobayashi, Andréa Regina Kaneko (Revista de Negócios, 2018)
Sustainable entrepreneurship emerges as one of the economically viable alternatives, with products and processes geared to the creation of solutions allied to social and environmental responsibility. The behavior of this literature arouses increasing interest. Thus, the objective of this study was to analyze the scientific production on sustainable entrepreneurship, on Web of Science, from 2000 to 2016. The study was exploratory, qualitative, inductive, documental, and bibliographic. The discourse analysis technique was adopted. Web of Science database was chosen due to the relevance and impact in the dissemination of science, and the categories â€œManagementâ€ and â€œBusinessâ€ and the filters â€œArticlesâ€ and â€œReviewâ€ were considered for the study. Thirty articles were identified as â€œcorpusâ€ of research and composed the intentional sample. The results indicate that 2010 and 2011 were the most productive years. Journal of Business Venturing, Impact Factor of 3,678, published seven articles, including the two most cited in this literature. It was possible to notice the increasing tendency of citation of the articles researched and the increase of the scientific production in the area, each year, in high Impact Factor journals. The results allowed to identify, characterize, report, and classify this literature. It was also possible to confirm the maturity rise of the authors in 2015 and 2016 regarding the most specific considerations presented in researches carried out in environmental or social contexts. Current and relevant, sustainable entrepreneurship is considered important for the Administration area of study.